Totally laparoscopic gastrectomy for gastric cancer: Meta-analysis of short-term outcomes. Issue 3 (May 2012) - Bracale, Umberto; Rovani, Marcella; Bracale, Marcello; Pignata, Giusto; Corcione, Francesco; Pecchia, Leandro
Abstract: Introduction: We present a review of the literature, together with a meta-analysis of short-term outcomes of totally laparoscopic gastrectomy (TLG) compared with open gastrectomy (OG). Material & methods: We carried out a search in the Pubmed and Cochrane databases from September 2003 to May 2009. Controlled studies on early outcomes were included, both prospective and retrospective, randomized and non-randomized. Results: We found nine eligible studies, one of which was a randomized controlled trial (RCT), while eight were series of patients (three consecutive). The study group consisted of 1, 492 patients, 828 of whom had been treated with TLG and 664 treated with OG. TLG for gastric cancer shows a 32.5% (p < 0.001) longer operative time than OG, whereas TLG demonstrated a 44% (p < 0.001) reduction in blood loss, a 34% (p < 0.001) reduction time to first flatus and a 33.7% reduced (p < 0.001) hospital stay. No notable differences were registered regarding morbidity and mortality rates, and no significant difference was observed between the two groups regarding the extent of the lymphadenectomy. Conclusions: Despite a longer operative time for TLG, with a gastrointestinal recovery rate faster than the OG one for gastric cancer results, no notable differences were recorded between the two techniques for the morbidity and mortality rates and in the spread of the lymphadenectomy.